POTENTIAL USE OF VIRTUAL REALITY IN OVERCOMING NEEDLE PHOBIA IN COVID-19 VACCINATION - Penggalih Mahardika Herlambang; Nanang Wiyono; Hendry Gunawan; Rani Tiyas Budiyanti (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Vaccination is very important because it can help prevent diseases that can be prevented by immunization (PD3I) such as polio, tetanus, diphtheria, measles, mumps, and rubella. During the Coronavirus Disease -19 (COVID-19) pandemic, the role of vaccination is very crucial, especially to reach herd immunity. However, there are many problems related to the implementation of vaccination, including needle phobia, which is a phobia of needles because it is considered painful. Virtual reality is a technology that develops in the form of a virtual image that can be used in vaccination services. This study aims to determine the potency of virtual reality to solve the needle phobia in vaccination services.Methods: The method used in this study is a literature review with sources from journals in the Scopus, ProQuest, and ScienceDirect database that was published in 2000 until 2020, and also books and articles with the keywords "virtual reality" "AND" "immunization," virtual reality " AND " vaccination " , "Needle phobia" "AND" "vaccination". This research was conducted from January to February 2021.Results: Based on the results obtained, virtual reality can be used in vaccination services, especially in the treatment of needle phobia. Virtual reality can become a distraction so that the patient will be distracted from fear and can lower the pain threshold. In addition, virtual reality can also be used as a means of education about immunization.Conclusion: Product development and clinical research need to be developed to assess the use of virtual reality in vaccination services during the COVID-19 pandemic. The use of virtual reality for other medical procedures that use needles can also be further investigated